PERANCANGAN SISTEM INFORMASI DAN REGISTRASI LOMBA AKADEMIK BERBASIS WEB - Yunita; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Education is very important for everyone because it can add insight, hone skills in solving problems, improve the economy, and get good job prospects in the future. Along with the times, the education needed is getting higher so that it requires universities in Indonesia to increase their knowledge. One thing that can be done is to encourage students to take part in the various competitions held. Therefore, the Design of Information Systems and Web-Based Registration of Academic Competitions aims to create a means to bring contest organizers together with potential participants who wish to develop their abilities. In developing the appearance of this website using HTML, CSS, Javascript and to connect the database itself using MySQL. With this website, it is hoped that it will be easier for students to participate in or get information regarding competitions that are being held, so that they can develop their potential